Poland's Labor Market : The Challenge of Job Creation - World Bank (Washington, DC, 2013)
The study reviews recent labor market developments in Poland, examining the factors behind the rise in unemployment, and, proposing actions that should contribute to increased job creation rates. Its main purpose is to inform - based on research findings - on the policy dialogue regarding the current labor market situation in the country. Those main findings indicate that the rise in unemployment results primarily from an acceleration of job destruction, that begun with the wave of enterprise restructuring in the aftermath of the Russia crisis, and has persisted in part, because of an imbalance in the fiscal-monetary policy mix. It also finds that the recent rise in unemployment has highlighted important barriers in the transition from old, to new jobs. These barriers include a binding minimum wage, high taxes on labor income, limitations in the labor code, and a relatively easy access to early retirement, and other social benefits. Additionally, the problems with the ongoing restructuring of the Polish labor market have been compounded by an increase in new labor market entrants, primarily recent school graduates joining the labor force, and, of particular concern are the new labor market entrants with only basic vocational education or less, namely in rural areas, given that educational attainment is a determining factor on employment status. The policy agenda needs to gradually address unemployment issues, through better fiscal-monetary policy mix, through greater flexibility in the wage structure, and, through tax reductions on labor income, and changes in the labor code. Moreover, investments in worker's education and training needs to be improved, realigning the incentives under labor market programs, and lowering the costs of starting, and running businesses.